2017
DOI: 10.1021/acs.organomet.7b00294
|View full text |Cite
|
Sign up to set email alerts
|

Side-Arm Control in Phosphine-Sulfonate Palladium- and Nickel-Catalyzed Ethylene Polymerization and Copolymerization

Abstract: A series of phosphine-sulfonate ligands bearing various side-arm substituents were designed and prepared. The corresponding Pd(II) complexes [κ 2 -(P,O)-2-(PPhAr)-1-benzenesulfonato]Pd(Me)(dmso) (Pd1, Ar = o-MeO-C 6 H 4 ; Pd2, Ar = o-PhO-C 6 H 4 ; Pd3, Ar = o-(2,6-Me 2 -C 6 H 3 )O-C 6 H 4 ; Pd4, Ar = o-PhSO 2 -C 6 H 4 ) and Ni(II) complexes [κ 2 -(P,O)-2-(PPhAr)-1-benzenesulfonato]-NiPh(PPh 3 ) (Ni1, Ar = o-MeO-C 6 H 4 ; Ni2, Ar = o-PhO-C 6 H 4 ; Ni3, Ar = o-(2,6-Me 2 -C 6 H 3 )O-C 6 H 4 ; Ni4, Ar = o-PhSO 2 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 63 publications
2
26
0
1
Order By: Relevance
“…The cooligomers also possess relatively linear structures. For example, the methyl acrylate was incorporated both in the main chain and in the terminal chain end (Figure S59) . No incorporation on the end of branches was observed.…”
Section: Resultssupporting
confidence: 75%
“…The cooligomers also possess relatively linear structures. For example, the methyl acrylate was incorporated both in the main chain and in the terminal chain end (Figure S59) . No incorporation on the end of branches was observed.…”
Section: Resultssupporting
confidence: 75%
“…[13] Such short metal-oxygen distances have been previously observed in some Group 10 phosphine-sulfonate complexes. [14] Moreover, during polymerization and after the dissociation of the coordinating DMSO or PPh 3 ,i nteractions that affect the polymerization or copolymerization processes might occur.…”
mentioning
confidence: 99%
“…Initial reports by Brookhart and co‐workers revealed that complexes of nickel and palladium bearing sterically hindered α‐diimine ligands could generate high‐molecular‐weight polymers with high catalytic activity in ethylene polymerization . The properties and reactions of metal complexes are highly dependent on the selection of supporting ligand(s), and this selection is one of the keys to successful coordination chemistry. Late transition metal catalysts based on bulky bis)imine(ligands usually depend on the structures of ligands and ortho ‐position groups on the aryl rings that showed very interesting behaviours in olefin polymerization .…”
Section: Introductionmentioning
confidence: 99%